The upside-down museum practice-based institutional critique, working up from the actual museum floor - Giannotti, Aldo 1977-; Steves, Andrea; Lomme, Freek ca. 20. Jh (Set Margins Press, 2024)
Verlag: "In defiant response to the mechanisms, habits, and status of the museum, artist Aldo Giannotti’s concepts and props, initially conceived in sketchbooks, transform into tangible institutional realities, reshaping the museum’s social and spatial architecture and sometimes literally breaking its walls. This realignment establishes accountability, on the spot and without holding back, to meet real needs. This is a practice-based institutional critique based in ongoing, in-person practice, working up from the actual floor. Through dialogue with the museum staff, guards, and visitors, Giannotti develops an inclusive engagement with the institution and its underlying purpose. The book surveys numerous cases and obstacles that threaten the sustainability of long-standing habits in museology. It emphasizes working on the ground rather than from office spaces, focusing on accountability in the very spaces where the museum functions. It presents a challenge to the art world, offers insight to those who passively endorse the existing order of public art, and serves as a mediator between current art workers and outdated art systems."
Keywords: Giannotti, Aldo -- 1977-; Bildband